Variational perturbative approach to bound magnetopolarons in parabolic quantum wires - Shi, Zhi Fei. (2011)
In this thesis, we have developed a general approach for studying the effect of a parabolic on the energy levels of a bound magnetopolaron in a quantum wire. We established the Hamiltonian of the bound magnetopolaron and used a variational perturbative method to find the solutions for the Hamiltonian. Our approach is reasonable for arbitrary values of electron-phonon coupling constant α, Rydberg constant R, parabolic potential frequency ω and cyclotron frequency ωc.